PENGGUNAAN INFORMASI ELEKTRONIK DAN DOKUMEN ELEKTRONIK SEBAGAI ALAT BUKTI PERSIDANGAN - P, Santhos Wachjoe (Jurnal Hukum dan Peradilan, 2016)
Court trials always refer to the rules contained in Law No. 8 1981 of the Criminal Code, which seem underdeveloped, mainly about the arrangements regarding evidence which can be used in the court. This paper outlines the use of a few electronic documents as evidence in the trial. Hopefully, this paper can provide enlightenment to the law enforcement authorities in carrying out their duties, particularly in the proceedings.Keywords : electronic information, electronic document, evidence